EFFECT OF PHYTOSTEROL EXTRACT FROM SESAME SEED ON EXPERIMENTALLY INDUCED HYPERLIPIDEMIC RATS: DOSE DEPENDENT STUDY - SHREOSHI MALLICK,; MEGHAMALA MANDAL,; SUCHISMITA ROY,; SHRABANI PRADHAN,; SHREYA MANDAL,; RAJ KUMAR MAITI,; DILIP KR. NANDI,; RUPA DASGUPTA,; KOUSHIK DAS, (International Journal of Pharma and Bio Sciences, 2016)
Hyperlipidimia is a medical condition where there is an elevation of lipids, or fats, in the blood. The purpose of the study was to evaluate the hypolipidemic effect of sesame seed on experimentally induced hyperlipidemic albino rats. The study was carried out with thirty Wistar stain albino male rats and the groups were Group I was denoted as control, they were provided normal food, water with 1g multi-vitamin for 60 days. Group II was denoted as hyperlipidemic, from 1st to 14th day they were provided normal food, water and on the 15th to 60th day (45 days) they were provided normal food with 3.7 ml coconut oil with 1mg/kg cholesterol per rat, 1g multi-vitamin, and 5% sucrose for induction of hyperlipidemia. Group III, Group IV, Group V were denoted as treatment I, I, III respectively and they were treated as group II rats and fed orally sesame seed extract at the dose of 25, 50 and 75 mg/kg body weight/day/rat orally for 45 days respectively. The result of the present study showed that the toxicity level and total fat content of liver, intestine, and adipose tissue were significantly decreased and the antioxidant enzyme profiles were significantly increased in treatment I, II and III groups than the hyperlipidemic group. Sesame seed (Sesamum indicum) is the rich natural sources of phytostreol which have great reducing capability for lowering the blood cholesterol, triglyceride level and total fat content of the different tissues.